Für einen wirksamen Schutz der Mutterschaft
politischer Rahmen;Wahlen und Abstimmungen;Volksabstimmung;Abstimmungskampf;Abstimmungsempfehlung politischer Rahmen;Wahlen und Abstimmungen;Volksabstimmung;Volksinitiative soziale Fragen;sozialer Schutz;Sozialurlaub;Erziehungsurlaub;Mutterschaftsurlaub soziale Fragen;sozialer Schutz;Sozialurlaub;Erziehungsurlaub;Vaterschaftsurlaub soziale Fragen;sozialer Schutz;Sozialversicherung;Mutterschaftsversicherung